Neuroradiological response criteria for high-grade gliomas - Lutz, Kira; Radbruch, Alexander; Wiestler, Benedikt; Bäumer, Philipp; Wick, Wolfgang; Bendszus, Martin (Clinical neuroradiology, 2011)
The recently introduced new response criteria of the response assessment in neuro-oncology (RANO) working group and its clinical implications are the topic of this article. Establishing this working group as a work-in-progress platform and its first report, the RANO criteria represent an important step forward in the accurate assessment of response to therapy in patients with malignant gliomas not only in clinical trials but also in daily practice. Anti-angiogenic therapy and other new treatment modalities have increased the incidence and awareness of novel imaging phenomena, such as pseudoprogression and pseudoresponse not only within clinical trials. The new RANO criteria also take clinical parameters, such as steroid medication and neurological symptoms into account. Neuroradiologists and neuro-oncologists need to be aware of and experienced in applying these new criteria to correctly assess the response to treatment in patients with malignant gliomas. Further research is needed to study new imaging techniques, such as perfusion and diffusion-weighted imaging and to investigate and incorporate these for routine tumor response criteria.